2020
DOI: 10.1302/1863-2548.14.190125
|View full text |Cite
|
Sign up to set email alerts
|

Follow-up of walking quality after end of growth in 28 children with bilateral cerebral palsy

Abstract: Purpose Assessment of surgical treatments on gait in patients with bilateral cerebral palsy (CP) is often performed in short-term studies. The purpose of this study was to analyze the influence of single-event multilevel surgery (SEMLS) on long-term evolution of gait using gait deviation index (GDI) and walking speed. Methods In all, 28 patients with bilateral CP (Gross Motor Function Classification System I to III) with two clinical gait analyses (CGA) were included (mean age: 9.0 years (sd 2.9) at the first … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

1
7
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 7 publications
(8 citation statements)
references
References 42 publications
1
7
0
Order By: Relevance
“…This revealed that patients who did not undergo surgery and had good gait function at baseline (10 patients at GMFCS level I) maintained their gait quality, whereas patients who underwent SEMLS (18 patients at GMFCS levels I and II) showed-in the majority of cases-improved gait quality at follow-up. 14 Thus, for both USCP and bilateral CP patients, the long-term beneficial impacts of surgery on gait quality are noteworthy, as measured using mGPS and GVS.…”
Section: Discussionmentioning
confidence: 99%
See 3 more Smart Citations
“…This revealed that patients who did not undergo surgery and had good gait function at baseline (10 patients at GMFCS level I) maintained their gait quality, whereas patients who underwent SEMLS (18 patients at GMFCS levels I and II) showed-in the majority of cases-improved gait quality at follow-up. 14 Thus, for both USCP and bilateral CP patients, the long-term beneficial impacts of surgery on gait quality are noteworthy, as measured using mGPS and GVS.…”
Section: Discussionmentioning
confidence: 99%
“…Similar results were observed in previous publications. 14,31 Examining this study cohort in more detail, only 18 patients had not undergone surgery after their initial CGA. We observed improvement or stabilization in the "no surgery" treatment group's mGPS on both their affected and unaffected sides but with no significant overall difference (Table 2).…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…The GDI and the GPS were developed for gait assessment of patients in general and not exclusively for CP patients [19,21,23,31,32]. Furthermore, the GGI and the GDI were suggested as an adequate parameter for follow-up evaluation of gait and correction procedures [33][34][35].…”
Section: Introductionmentioning
confidence: 99%